ANTHROPOMETRIC AND BODY COMPOSITION DIFFERENCES AMONG ELITE MACEDONIAN`S SOCCER AND HANDBALL PLAYERS - Zikica Tasevski (My University, 2020)
The comparative researches on athlete’s anthropometric characteristics are undoubtedly important in modern sport, and they have been studied for a long time by a considerable number of sports scientists from many countries. However, only a few studies that address this topic have been conducted on Macedonian athletes. The present research was conducted on 181 elite players divided in two groups as follows: 91 handball players and 90 soccer players. The respondents were measured for their height, weight, diameters, volume and skinfolds; the body composition, somatotype components and BMI - index were indirectly calculated with the purpose of establishing their common morphological characteristics, and to analyzing the specificity, i.e. probable differences according to the sport. Breadth and girth values were evaluated by ANCOVA, and height and weight were used as co-variate factors. The other variables were rated by metric ANOVA. The research results suggest that the soccer players are shorter and have lower body weight as compared to handball players, their BMI is statistically considerably lower compared to that of handball players. Soccer players have higher relative girth of the lower extremities, and smaller values of all skinfolds and lesser percentage of the fat component as compared to the handball players. The mesomorphic component dominates in general with the soccer players, and their somatotype category is a balanced mesomorph, whereas the one-mesomorph type is obtained with handball players.
Keywords: Anthropometry, physical differences, somatotype, sports